Kelimpahan Bakteri Selulolitik di Muara Sungai Gunung Anyar Surabaya dan Bancaran Bangkalan [The Total of Cellulolytic Bacteria in Gunung Anyar Surabaya and Bancaran Bangkalan Estuaries ] - Moch. Amin Alamsjah; Didya Sinatryani; Sudarno Sudarno; Kustiawan Tri Pursetyo (Jurnal Ilmiah Perikanan dan Kelautan, 2014)
Abstract Most organic materials utilized mangrove detritus such as mangrove leaves fall throughout the year. Organic particles or litter into a place to live for bacteria, fungi and other microorganisms. One of organic compounds in the soil is cellulose. Deciduous leaves on the ground allows that the cellulose content in the soil is high, it is possible to find cellulose degrading bacteria in the mangrove ecosystem. Soil sampling conducted in April 2014 located in Gunung Anyar Surabaya estuaries and Bancaran Bangkalan estuaries. After taking the samples, the isolation of cellulolytic bacteria and bacteria calculation were conduct using standard Total Plate Count (TPC). Based on the results of the calculation of total number bacteria, obtained the highest total number of cellulolytic bacteria at station E (Bancaran) of 4.9 x 104 CFU/ml. The highest percentage of cellulolytic bacteria obtained at station D (Bancaran) with a percentage of 27.09%. According to the whole calculation of the total number of bacteria, total number and percentage of cellulolytic bacteria, it was found that the area of Bancaran Bangkalan has higher abundance of cellulolytic bacteria than Gunung Anyar Surabaya mangrove areas.